Exploring the relationship between corporate ESG information disclosure and audit fees: evidence from non-financial A-share listed companies in China - Zhang, Kaimeng; Liu, Xihe; Wang, Jingjing (Frontiers in Environmental Science, 2023)
ESG information disclosure is an essential aspect of corporate ESG responsibility and has gained significant attention in the context of ecological civilization development within the socialist market economy. However, in China's early stage of ESG development, challenges such as ESG rating discrepancies, "greenwashing," and corporate "cleansing" accompany ESG information disclosure. This study aims to investigate the impact of corporate ESG information disclosure on audit fees using a sample of non-financial A-share listed companies in China from 2011 to 2020. Drawing on the "deep pocket" theory, risk premium theory, and cost-benefit principle, the research examines the relationship between ESG information disclosure and audit fees. The findings reveal that approximately one-third of Chinese enterprises disclose ESG information, and substantial variation exists in the disclosure scores among the disclosed firms. The empirical analysis further demonstrates that firms disclosing ESG information tend to face higher audit fees, with higher ESG disclosure scores associated with increased audit fees. Moreover, an increase in the disclosure score of any ESG dimension (environment, social responsibility, and corporate governance) leads to higher audit fees. The study also identifies operational risk as a mediating factor in the relationship between ESG disclosure and audit fees. Additionally, media attention can dampen the positive effect of ESG disclosure scores on audit fees. Furthermore, the impact of ESG disclosure scores on audit fees is more pronounced in firms that voluntarily disclose ESG information before the implementation of the new Environmental Protection Law. These findings contribute to the literature and provide theoretical insights for governmental and regulatory decision-making, corporate managers, auditors, and ESG investors in China.